Randomised, controlled trial of alternating pressure mattresses compared with alternating pressure overlays for the prevention of pressure ulcers: PRESSURE (pressure relieving support surfaces) trial. Issue 7555 (1st June 2006) - Nixon, Jane; Cranny, Gillian; Iglesias, Cynthia; Nelson, E Andrea; Hawkins, Kim; Phillips, Angela; Torgerson, David; Mason, Su; Cullum, Nicky
Abstract: Objective To compare whether differences exist between alternating pressure overlays and alternating pressure mattresses in the development of new pressure ulcers, healing of existing pressure ulcers, and patient acceptability. Design Pragmatic, open, multicentre, randomised controlled trial. Setting 11 hospitals in six NHS trusts. Participants 1972 people admitted to hospital as acute or elective patients. Interventions Participants were randomised to an alternating pressure mattress (n = 982) or an alternating pressure overlay (n = 990). Main outcome measures The proportion of participants developing a new pressure ulcer of grade 2 or worse; time to development of new pressure ulcers; proportions of participants developing a new ulcer within 30 days; healing of existing pressure ulcers; and patient acceptability. Results Intention to treat analysis found no difference in the proportions of participants developing a new pressure ulcer of grade 2 or worse (10.7% overlay patients, 10.3% mattress patients; difference 0.4%, 95% confidence interval - 2.3% to 3.1%, P = 0.75). More overlay patients requested change owing to dissatisfaction (23.3%) than mattress patients (18.9%, P = 0.02). Conclusion No difference was found between alternating pressure mattresses and alternating pressure overlays in the proportion of people who develop a pressure ulcer. Trial registration ISRCTN 78646179